Representation and processing of lexical bundles: Evidence from word monitoring. (February 2019) - Jeong, Hyojin; Jiang, Nan
Abstract: The present study examined the holistic representation and processing of lexical bundles in second language (L2) learners of English and native English speakers. This holistic hypothesis suggests that multiword units such as formulaic sequences are represented as single units and retrieved directly from the mental lexicon as wholes and some evidence has become available for the hypothesis (e.g. Jiang & Nekrasova, 2007). However, findings are not clear with respect to lexical bundles. The paper begins with a classification of different types of multiword units, highlighting the differences between formulaic sequences and lexical bundles. To examine if the holistic hypothesis applies to the latter, L2 learners and the native speakers of English were tested using a word monitoring task. The results replicated a formula advantage found in earlier research, but the participants did not respond to lexical bundles faster than the controls for both groups. Potential explanations are discussed about the differences between formulaic sequences and lexical bundles in mental representation.